POSITIVE DEVIANCE SEBAGAI METODE PENDEKATAN MENGONTROL KADAR GULA DARAH PENDERITA DIABETES MELITUS - Nur Setia Dewi, Mariyati, (STIKES Widya Husada Semarang, 2012)
POSITIVE DEVIANCE AS A METHOD OF APPROACH BLOOD SUGAR CONTROL PEOPLE WITH DIABETES MELLITUSÂ Diabetes mellitus Monitoring to control of blood sugar levels as normal as possible conditions. Management of Diabetes mellitus consists of four pillars, namely education, food management, physical exercise and pharmacology intervention. In this study using the Positive Deviance approach to apply the method of the four pillars DM that is expected to lower blood sugar levels. Positive Deviance (PD) is an approach to solve problems that exist in a community-based society. The aim is to determine the effect of positive deviance on blood sugar levels in people with diabetes mellitus. This study is a quantitative experimental study design with pre-experimental one group pretest-posttest design. Populasi in this study that patients with DM aged 50-65 years at the health center Banyumanik Padangsari district, Semarang. Sampling method using random sampling involving 22 respondents. The average blood sugar levels before the intervention of 22 respondents is 229.55 mg /dl, SD value is 79.307 with a value of blood sugar levels ranged 132-391 mg /dl. Average blood sugar levels after the intervention of 22 respondents is 173.73 mg /dl, SD is 56.941 with a value of blood sugar levels ranged 126-306 mg /dl. Test the effect of positive deviance on blood sugar levels using a paired sample sign test obtained a mean value = 0.001, p value <0.05. There is a positive deviance effect on blood sugar levels in people with diabetes mellitus in the health center Padangsari Banyumanik Semarang. Keywords: Diabetes Mellitus, blood sugar levels , positive deviance